EMPOWERING STUDENTS’ LANGUAGE COMPETENCE AND CULTURAL AWARENESS THROUGH COMMUNICATIVE APPROACH - Mantra, Ida Bagus Nyoman; Maba, Wayan; Wedasuwari, Ida Ayu Made; Staupelyte, Agne (International Journal of Social Science, 2024)
The communicative approach to learning language aims to improve students' communication skills, both orally and in writing. This approach focuses on developing four language skills: listening, reading, speaking, and writing. In the communicative approach, students can use language actively in communicative situations. This study used classroom action research to improve students' language competence and cultural awareness by implementing a communicative approach. Data from the study were collected through pretest, post-test, and questionnaire. The results showed that the student's language competence and cultural awareness improved significantly through a communicative approach. Therefore, communicative learning is effective for improving language competence and cultural awareness. This study implies that teachers should consider using a communicative approach in developing students’ language competence and cultural awareness.